The multifaceted biology of lncR-Meg3 in cardio-cerebrovascular diseases - Li, Jing; Liu, Wenxiu; Peng, Fu; Cao, Xiaoyu; Xie, Xiaofang; Peng, Cheng (Frontiers in Genetics, 2023)
Cardiocerebrovascular disease, related to high mortality and morbidity worldwide, is a type of cardiovascular or cerebrovascular dysfunction involved in various processes. With the advent of aging era, this crisis exacerbates and causes a huge economic burden for individual and government. In recent years, the so-called long noncoding RNAs (lncRNAs), are reported to be associated with the incidence of many maladies. The identification of imprinted maternally expressed gene 3 (MEG3) on the human chromosome 14q32 has initiated an upsurge in research since 2000. A great deal of evidence supports that MEG3 imprinted gene is incapable to encode functional proteins,but exhibits a regulatory role mostly through a long non-coding RNA, named lncR-Meg3. With the advancements in sequencing technologies, intricate mechanisms underlying this matter are being elucidated from epigenetic, transcriptional and post-transcriptional aspects. Among these mechanisms, apoptosis, fibrosis, inflammation and angiogenesis have been implicated in distinct diseases and contribute a lot to pathological development. This review aims to outline the versatile functions of lncR-Meg3 in a plethora of cardiocerebrovascular diseases, hoping to provide novel insights in clinical applications.